2012
DOI: 10.1111/j.1744-6198.2012.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Academic Integrity Among Nursing Students

Abstract: We recommend fostering culture change through strategies that target students, faculty, and systems. These strategies include peer mentoring, role modeling integrity, enhancing awareness of what constitutes cheating, and developing policies that promote honesty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…The review of the literature has revealed that academic dishonesty is a complex and wide-spread phenomenon that also reachesinto the context of the nursing formation. This phenomenon is a source of worry for the scientificnursing community because of the positive correlation that has emerged betweenacademic misbehaviours and future ethical professional behaviour (Nonis and Swift, 2001;Kenny, 2007;Woith et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of the literature has revealed that academic dishonesty is a complex and wide-spread phenomenon that also reachesinto the context of the nursing formation. This phenomenon is a source of worry for the scientificnursing community because of the positive correlation that has emerged betweenacademic misbehaviours and future ethical professional behaviour (Nonis and Swift, 2001;Kenny, 2007;Woith et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more recentstudies have established that academic dishonesty is now also a common phenomenon among student nurses (Bailey, 2001;Brown, 2002;McCabe, 2009;Krueger,2014;Stonecypher&Willson, 2014).The importance of these studies for nursing resides in determining the potential risk of dragging unethicalbehavior acted out in class into clinical practice, creating a threat tothe safety and wellbeing of the patients (Bailey, 2001;Woith et al, 2012;Krueger, 2014).…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study, Jenkins and colleagues reported students identified overtly rude behaviors among their peers, such as eye-rolling, snickering, and talking while others were speaking [3] . Students have also described an atmosphere of academic competition in which peers refused to help others study and intentionally provided them with erroneous information [14] . Incivility is a significant problem in clinical settings as well; students have reported being ignored and treated unfairly by hospital nurses [15] .…”
Section: Incivility and Nursing Educationmentioning
confidence: 99%
“…[8,9] Particularly, nursing professors are in charge of spreading and preserving the standards of research ethics as the nonfulfillment of these standards may have pernicious consequences on patients' lives. [10] There is an urgent need to identify the knowledge and attitudes of researchers towards plagiarism and scientific misconduct, [11] while plagiarism will never be vanquished until the institutional control is required to reduce it. [12] Additionally, academic misconduct in the scientific nursing researches can seriously harm the people's life and health, so it needs a great accountability.…”
Section: Introductionmentioning
confidence: 99%